Effects of substituting ytterbium for scandium on the microstructure and age-hardening behaviour of Al-Sc alloy - Tuan, N. Q.; Pinto, A. M. P.; Puga, H.; Rocha, L. A. [UNESP]; Barbosa, J. (Elsevier B.V., 2014)
In order to reduce the cost of Al-Sc alloys and maintain their mechanical properties, the microstructure and mechanical properties of Al-0.24 wt% Sc-0.07 wt% Yb in comparison with Al-0.28 wt% Sc alloys were studied. The aging behaviour, precipitate morphologies, precipitate coarsening and precipitation hardening of both alloys were investigated. The average diameter and the size distribution of nanoscale Al3Sc and Al-3(Sc,Yb) precipitates at various aging conditions were measured. Transmission electron microscopy (TEM) and high-resolution TEM were used to deeply understand the precipitate evolution. A maximum hardness around 73 (HV30) was obtained with a precipitate diameter from 4.3 to 5.6 nm for both alloys. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Aluminium-scandium alloys; Ytterbium; Age-hardening; Precipitate coarsening; TEM; High-resolution TEM